Improving Tourist Loyalty: Examining the Role of Environmental Tourism Policy on Tourist Behavior - NOVITANINGTYAS, Ivo; LIONORA, Clarisa Alfa; ACHSA, Andhatu; HARTONO, Budi (Journal of Environmental Management and Tourism; Vol 15 No 3 (2024): JEMT, Volume XV, Issue 3(75), Fall 2024DO - 10.14505/jemt.v15.3(75).09, 2024)
Purpose: This research aims to develop a model of tourist loyalty based on relationship marketing theory and consumer decision-making model. Moreover, this research also aims to examine the effect of implementing the CHSE certification policy on tourist satisfaction and loyalty in the context of the hospitality business in the tourism area around Borobudur Temple. Methodology: This research uses a quantitative approach. The primary data collection method uses a questionnaire distributed to 212 tourists as respondents who were selected based on the purposive sampling method. Data were analyzed based on PLS-SEM using Smart-PLS 3. Findings: The research results show that implementing CHSE certification in the hospitality industry can increase tourist satisfaction and tourist loyalty. Aspects of cleanliness, health and environmental sustainability have a positive influence on tourist satisfaction and loyalty, although safety aspects have not shown a significant influence. Originality: Although studies on tourist loyalty are abundant, empirical research that focus on examining the influence of tourism policy on tourist loyalty are still rare. This research therefore serves as one of the first attempts to examine the influence of tourism policy on tourist behavior (tourist satisfaction and tourist loyalty) in the context of the hospitality industry, in Indonesia. Research Implication: The research results provide managerial implications for hospitality businesses to implement CHSE certification to satisfy tourists and their loyalty. By having loyal tourists, it is hoped that the tourism business can develop and be sustainable.